Restoring semi-natural grasslands in Central Europe with plant material transfer – achievements, success factors, and knowledge transfer - Sommer, Leonhard; Justus Liebig University Giessen (My University, 2025)
Since the industrial revolution, land use changes and intensification of use have drastically reduced the area of species-rich, semi-natural grasslands in Central Europe. Active restoration of these ecosystems is therefore necessary and increasingly demanded by legislation. One method to (re-)introduce target plant species is the transfer of seed-containing plant material cut from species-rich, semi-natural donor sites. Given the urgency of the restoration task, the aim of this thesis is to contribute to understanding the success factors of this method, particularly in practice. In a first study, 20 recipient sites of floodplain meadow restoration in Hesse, Germany, were revisited and investigated for vegetation composition in comparison to their corresponding donor sites 13-16 years after plant material transfer. To assess the potential for livestock feeding, biomass yield and energy contents were measured, too. In a second study, 41 recipient-donor site pairs from practical grassland restoration projects in different regions of Germany and Luxembourg spanning a broad moisture gradient were investigated. Vegetation was recorded, and soil analyses and information on restoration from the practice partners were used for success factor identification. In a third study, 33 practitioners of grassland restoration with plant material transfer were interviewed to compare their views on the topic to European scientific literature. All three studies underline the critical importance of abiotic site conditions supporting the target plant communities. A frequent long-term problem is too high productivity of recipient sites, particularly in floodplain meadows. Site conditions, along with competition for the introduced plant species, are strongly dependent on the previous state of recipient sites. Raw soils, e.g., obtained by topsoil removal, provide low-competitive, nutrient-poor conditions, often enhancing restoration success. Generally, competition for the introduced species is lowered by adequate soil preparation, whose effect may, however, diminish over time. Harvest time for the plant material is decisive for the pool of transferable target species, and supplementing this pool by additional introduction methods, such as sowing, is useful. For maintenance of restored grassland communities, appropriate low-intensive post-restoration management is necessary. Sufficient biomass yield and energy content enable integration in feeding rations for livestock, buffering the costs of management. Practitioner interviews revealed that overarching factors such as project organisation, trust-building, and experience strongly influence how well the previously mentioned conditions can be met. To support grassland restoration in the coming decades, a challenge increased by climate change, intense knowledge exchange between science and practice and among practitioners is advised.
Keywords: ddc:333.7; ddc:630